Mathematical modeling of the folded foundation interaction with the base by varying the structure stiffness - Timchenko, Radomir; Krishko, Dmytro; Khoruzhenko, Iryna (Academic journal Industrial Machine Building Civil Engineering, 2018)
The article describes a practice of using software system based on the finite element method for calculating shell foundations. It considers the peculiarities of the folded foundation interaction with subsoil mathematical modeling . It is found that during modeling, special attention should be paid to a purpose of the system initial parameters, to a choice of finite elements type, and to an optimal model of subsoil. Mathematical modeling of the folded foundation interaction with subsoil is performed under conditions of a plane problem. The foundation operation under various conditions of interaction with subsoil and with different stiffness parameters of the foundation is analyzed. Correlation between stiffness of a foundation structure and resulting equivalent stresses in subsoil under different conditions of interaction is determined. It is concluded that the obtained results represent a benchmark for subsequent calculations and modeling the interaction between a foundation and subsoil under a volumetric stressed condition.
Keywords: shell foundation; finite element method; mathematical modeling; coulomb-mohr model